2017
DOI: 10.1111/gtc.12489
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐dependent expression of synapse‐related proteins in the mouse brain

Abstract: A synapse is a cell adhesion structure that permits a neuron to pass a chemical or electrical signal to another neuron. They connect neurons and form neural networks that are essential for brain functions, such as learning and memory. At a chemical synapse, the presynapse and the postsynapse are connected by cell adhesion molecules. The presynapse contains synaptic vesicles and their release machinery, whereas the postsynapse contains postsynaptic densities and receptors for the neurotransmitters. Many protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…In addition, Na + channel β-4 subunit and unphosphorylated tubulin β 3 class III proteins increase in the mouse brain during the postnatal and perinatal period, respectively (Fanarraga, L., Avila, J., & Zabala, J.C., 1999;Zhou, Zhang, Liu, Zhang, & Jiao, 2012). KCC2 mRNA and five synapse-related proteins are upregulated in the postnatal period (Clayton et al, 1998;Shiotani et al, 2017), and we showed their developmental regulation in the Xenopus tadpole brain during metamorphosis climax. The reduced expression level in the brain of hypothyroid rodents and the accumulation of mRNA stimulated by THs have been demonstrated for myelin-associated glycoprotein (Rodriguez-Peña et al, 1993), myelin basic protein (Ibarrola & Rodríguez-Peña, 1997), Na + ,K + -ATPase α2 (Chaudhury, Bajpai, & Bhattacharya, 1996) and neurofilament light and medium genes (Ghosh, Rahaman, & Sarkar, 1999).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, Na + channel β-4 subunit and unphosphorylated tubulin β 3 class III proteins increase in the mouse brain during the postnatal and perinatal period, respectively (Fanarraga, L., Avila, J., & Zabala, J.C., 1999;Zhou, Zhang, Liu, Zhang, & Jiao, 2012). KCC2 mRNA and five synapse-related proteins are upregulated in the postnatal period (Clayton et al, 1998;Shiotani et al, 2017), and we showed their developmental regulation in the Xenopus tadpole brain during metamorphosis climax. The reduced expression level in the brain of hypothyroid rodents and the accumulation of mRNA stimulated by THs have been demonstrated for myelin-associated glycoprotein (Rodriguez-Peña et al, 1993), myelin basic protein (Ibarrola & Rodríguez-Peña, 1997), Na + ,K + -ATPase α2 (Chaudhury, Bajpai, & Bhattacharya, 1996) and neurofilament light and medium genes (Ghosh, Rahaman, & Sarkar, 1999).…”
Section: Discussionmentioning
confidence: 83%
“…The synapse plays a pivotal role in chemical and electrical signal transmission from one neuron to another to maintain the functions of the nervous system including learning, memory and locomotion. The developmental levels of synapse-related proteins in the mouse brain have been reported (Shiotani et al, 2017), including several proteins that peak at P14 when TH levels are at their maximum. qRT-PCR analysis was conducted to examine the developmental expression profiles of five synapse-related genes, necl-1, necl-2, nectin-1, nectin-3 and PSD-95.…”
Section: Resultsmentioning
confidence: 99%
“…They were characterized as follows. Rat anti‐nectin‐2α/δ monoclonal Ab (mAb) (RRID:AB_590848) recognized 56‐kDa and 68‐kDa bands in Western blotting of mouse heart and brain (Aoki et al, ; Miyata et al, ; Shiotani et al, ). Specificity was verified by Western blotting of the wild‐type and nectin‐2 ‐deficient mouse hearts and cultured astrocytes and by immunohistochemistry on the wild‐type and nectin‐2 ‐deficient mouse hearts and brains (Miyata et al, ; Satomi‐Kobayashi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Specificity was verified by Western blotting of the wild‐type and nectin‐2 ‐deficient mouse hearts and cultured astrocytes and by immunohistochemistry on the wild‐type and nectin‐2 ‐deficient mouse hearts and brains (Miyata et al, ; Satomi‐Kobayashi et al, ). Rat anti‐nectin‐3 mAb (RRID:AB_592587) recognized a 90‐kDa band in Western blotting of mouse brain (Miyata et al, ; Satoh‐Horikawa et al, 2000; Shiotani et al, ). Specificity was verified by Western blotting of the wild‐type and nectin‐3 ‐deficient mouse brains and by immunohistochemistry on the wild‐type and nectin‐3 ‐deficient mouse brains (Honda et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation